The Impact of Organizational Climate, Knowledge Management, Ethical Leadership and Quality of MAIS on Firm Performance - Tauperta Siregar; Murtanto; Muhammad Nuryatno (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2023)
The purpose of this study is to prove the direct impact of organizational climate, knowledge management, ethical leadership and quality of MAIS on firm performance. The method used is a survey method for manufacturing companies in the Jakarta, Bogor, Depok, Tangerang and Bekasi areas. Respondents were selected with the criteria of a minimum position of supervisor to represent their respective companies. The number of samples that fit the criteria were 296 respondents. Data was tested by multiple regression analysis, using Smart PLS Software. Research proves that knowledge management, ethical leadership and quality of MAIS have a positive effect on firm performance. The highest impact comes from ethical leadership, then knowledge management, and finally the quality of MAIS. While organizational climate has no effect on firm performance. The implication is, if a company wants to improve firm performance, strategic actions can be sequenced by taking the following actions: improving ethical leadership, increasing knowledge management, and improving quality of MAIS.